Bilateral Renal Hilar Nutcracker Phenomenon in a Male Cadaver - Borthakur, Dibakar; Kumar, Rajesh; Dhawan, Vidhu; Dada, Rima (Acta medica Lituanica, 2024)
Nutcracker phenomenon (NCP) typically refers to the entrapment of the left renal vein (LRV) between the aorta and the superior mesenteric artery. Similar to the classic NCP, the renal vein can also get entrapped between the segmental branches of the renal artery at the renal hilum, which has been referred to as ‘renal hilar nutcracker phenomenon (RHNP).’ During routine dissection of a male cadaver of 67 years, the renal veins of both sides at the renal hilum were seen between the segmental branches of renal arteries, which we identified as the ‘renal hilar nutcracker phenomenon.’ The disposition of the rest of the perihilar structures was normal. ‘Renal hilar nutcracker phenomenon’ can have similar clinical presentation like that of the nutcracker phenomenon. Hence, knowledge of such anatomical variation at the renal hilum is desirable.
Keywords: Renal hilar nutcracker phenomenon; renal hilum; renal artery; renal vein